Childfree Perspectives Among Urban Muslim Youth in Indonesia : Insight From Feminist and Indonesian Progresive Islam Perspective - Najmi, Renci; Jennifer Nahyu, Kim; Fikri Ramadhan, An-Najmi; Abadi, Mansurni (Pusat Pengkajian dan Pengembangan Islam Jakarta (PPIJ), 2025)
This study investigates the childfree decision among urban Muslim youth in Indonesia, focusing on the negotiation between contemporary personal autonomy, patriarchal traditions, and religious expectations. Employing a qualitative methodology centered on discourse analysis, the research utilizes a dual framework of feminist theory and progressive Islamic interpretation. It explores the interaction between feminist ideals of reproductive rights and gender equality and the religious discourses of Indonesia's two largest Islamic organizations, Nahdlatul Ulama (NU) and Muhammadiyah. The findings indicate that NU adopts a conditional, permissible (mubah) stance on childfree choices when justified by health or economic considerations, whereas Muhammadiyah embraces more progressive, modernist perspective that frames the decision as a matter of social responsibility. From a feminist standpoint, the childfree choice is conceptualized as an assertion of autonomy and resistance to the patriarchal